2009
DOI: 10.1158/1535-7163.mct-09-0381
|View full text |Cite
|
Sign up to set email alerts
|

Molecular predictors of response to a humanized anti–insulin-like growth factor-I receptor monoclonal antibody in breast and colorectal cancer

Abstract: The insulin-like growth factor-I receptor (IGF-IR) pathway is required for the maintenance of the transformed phenotype in neoplastic cells and hence has been the subject of intensive drug discovery efforts. A key aspect of successful clinical development of targeted therapies directed against IGF-IR will be identification of responsive patient populations. Toward that end, we have endeavored to identify predictive biomarkers of response to an anti-IGF-IR-targeting monoclonal antibody in preclinical models of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 42 publications
(40 reference statements)
3
77
1
Order By: Relevance
“…The most significant amplified locus harbors IRS2. High IRS2 mRNA expression has been previously shown to correlate with response to an IGF1R monoclonal antibody in breast and colon cancer cell lines (21). The 17q22-24 amplification harbors 42 significant genes including those that encode the human growth hormones, GH1 and GH2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant amplified locus harbors IRS2. High IRS2 mRNA expression has been previously shown to correlate with response to an IGF1R monoclonal antibody in breast and colon cancer cell lines (21). The 17q22-24 amplification harbors 42 significant genes including those that encode the human growth hormones, GH1 and GH2.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in identifying predictors of response to anti-IGF1R therapy (20)(21)(22). The aim of this study was to identify biomarkers predictive of clinical efficacy with the IGF1R inhibitor, figitumumab, to help identify patient subgroups that may benefit from this type of targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that the level IGF-1R expression, which is associated with response to therapy, is rather low (10000-30000 receptors per cell) [18,19]. In addition, there is normal physiological IGR-1R expression in a number of tissues, such as colon, lung, pancreas, salivary gland, and stomach (http://www.proteinatlas.org).…”
Section: Introductionmentioning
confidence: 99%
“…This edition of Molecular Cancer Therapeutics includes an important report detailing a comprehensive preclinical evaluation of predictive biomarkers for h10H5 (Genentech, South San Francisco, CA), a humanized monoclonal antibody to IGF-IR (9). The identification of such biomarkers remains arguably the most important issue in development of drugs targeting IGF-IR.…”
mentioning
confidence: 99%
“…Studies of an IGF-IR tyrosine kinase inhibitor, NVP-AEW541, reported high levels of IGF-IR in all breast cancer cell lines evaluated with a high level of IRS1-I in the most sensitive of the cells (13). Zha and colleagues report differences in predictors of sensitivity for breast cancer and CRC cell lines, with IGF-IR mRNA expression being more predictive in breast cancer than in CRC (9). Furthermore, a 60-gene predictive expression signature was identified for the CRC cell lines with no predictive signature being identified for the breast cancer cell lines.…”
mentioning
confidence: 99%